Experiences influencing ethno-national identity learning: The case of young adults on the divided island of Cyprus - Christos Anagiotos (Adult Education Research Conference, 2017)
Due to nationalist conflict Greek-Cypriots and Turkish-Cypriots have lived apart from 1974 until 2003. This study investigates ethno-national identity learning as a lifelong learning process among young adults that were raised during the segregation period.
Keywords: Dewey; Cyprus; ethnic national identity; conflict; young adults